A Review of Flatfish (Order: Pleuronectiformes) Diversity in Indian Waters: A Literature Overview - Pillai, Honey Unnikrishna; Dutta, Sayani (Zootaxa, 2024)
The present study provides a comprehensive overview of the taxonomic diversity of flatfish in Indian waters. Flatfish play a significant role in artisanal and commercial fisheries in India and are frequently caught as by-catch in trawling operations. However, their benthic nature makes them particularly vulnerable to the pressures of overfishing and bottom trawling practices. Approximately 13% of all documented flatfish species worldwide have been recorded from India, contributing significantly to the global diversity, which includes 815 species across 124 genera and 14 families. Based on available literature, this study documented 108 flatfish species from India, represented by 35 genera in 10 families. The most dominant families identified were Cynoglossidae, Bothidae, Soleidae, and Paralichthyidae. Among the four major oceanic boundaries of India-the Arabian Sea, the Bay of Bengal, the Andaman and Nicobar regions, and the Lakshadweep waters, the Bay of Bengal was identified as having the highest recorded diversity of flatfish species. According to the IUCN classification, approximately 71 species reported from India are categorized as “Least Concern,” 34 as “Data Deficient,” two species as “Vulnerable,” and one species as “Near Threatened.” One species, Paraplagusia blochii, is still not assessed.